The importance of raiding ecology and sex differences in offensive and defensive warfare. (2019) - Lopez, Anthony C.
Abstract: De Dreu and Gross offer a compelling synthesis of a growing literature on the psychology of attack and defense. I argue that human raiding ecology suggests the need to endogenize attacker-defender move order as well as opportunities for tactical mismatch available to defenders. Perhaps most significantly, I draw attention to the surprising lacunae in sex differences across attack and defense.